1983
DOI: 10.1007/bf00965195
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acetylcholinesterase molecular forms in slow and fast muscle of rat

Abstract: Multiple molecular forms of acetylcholinesterase (AChE EC 3.1.1.7) from fast and slow muscle of rat were examined by velocity sedimentation. The fast extensor digitorum longus muscle (EDL) hydrolyzed acetylcholine at a rate of 110 mumol/g wet weight/hr and possessed three molecular forms with apparent sedimentation coefficients of 4S, 10S, and 16S which contribute about 50, 35, and 15% of the AChE activity. The slow soleus muscle hydrolyzed acetylcholine at a rate of 55 mumol/g wet weight/hr and has a 4S, 10S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Previous studies showed that denervation leads to a decrease in AChE activity, which then is resurrected during the reinervation stage. [50][51][52] Some data also suggest that this activity is homogenously present within muscle fibers regardless of the stage of regeneration. 53,54 However, in our study, we found that the activity of AChE, was localized predominantly within the fiber membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that denervation leads to a decrease in AChE activity, which then is resurrected during the reinervation stage. [50][51][52] Some data also suggest that this activity is homogenously present within muscle fibers regardless of the stage of regeneration. 53,54 However, in our study, we found that the activity of AChE, was localized predominantly within the fiber membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of AChE activity, which is a crucial component of the neuromuscular junction responsible for degradation of the neurotransmitter acetylcholine, was analyzed by the Karnovsky‐Roots method. Previous studies showed that denervation leads to a decrease in AChE activity, which then is resurrected during the reinervation stage …”
Section: Discussionmentioning
confidence: 99%
“…A series of studies recently performed in rodents (rat, mouse, and rabbit) has revealed that G, is closely related to the dynamic state ofthe skeletal muscle. Indeed, whereas slow-twitch muscles contain only a minimal amount of tetramer, fast muscles characteristically exhibit high levels ofG, (Bacou et al, 1982;Gisiger and Stephens, 1982Groswald and Dettbam, 1983). Furthermore, according to a recent report (Gisiger and Stephens, 1988) this additional pool is concentrated at the perijunctional sarcoplasmic reticulum, where it forms a cojunctional compartment embedding the neuromuscular junctions in an AChE-rich environment.…”
Section: Kecelvedmentioning
confidence: 99%
“…Although the significance of the different molecular forms remains unclear, their tissue-specific distributions are thought to reflect the physiological functions of the different tissues (Massoulie and Bon, 1982). For example, different distributions of AChE molecular forms have been reported to be correlated with the contractile activity of slow and fast rat muscle (Gisiger and Stephens, 1983;Groswald and Dettbarn, 1983;Lgmo et al, 1985).…”
mentioning
confidence: 99%